IRIS-TONED DECORATIVE PAPER - MISAWA YUTEN; ITOU KEIICHI; HAYAKAWA MINEO (1994)
PURPOSE:To provide the subject paper excellent in designability. CONSTITUTION:Hologram films are made into a powdery or fine chipped form, which is then dispersed in a composition comprising a binder and an organic solvent into a dispersion. This dispersion is then applied on base paper for decorative laminates to obtain the objective decorative paper. The amount of the powdery or fine chipped form to be dispersed is 10-60wt.% based on the composition.